Morphological Characterization of Local Ambon Bananas in the Highlands Rejang Lebong Regency - , M. Arzandy Marsal; Mardia Apriani; Rizky Septika Utami; Adnan; Rini Suryani; Parwito, Parwito (Jurnal Agricultural Science, 2023)
Curup local ambon bananas need to be developed and preserved so they don't lose their germplasm. Therefore, an exploration and characterization was carried out to obtain the types of local Ambon bananas in the highlands of Rejang Lebong district. This research was conducted from May to July 2023 in 4 Village Districts, namely Bermani Ulu District, Sukarami Village, Curup Tiimur District, Kampung Delima Village, Curup Utara District, Lubuk Kembang Village, and Selupu Rejang District, Pal Batu Village, Rejang Lebong District. The materials used in the study this is a sample of a banana plant. The method used is a direct survey to the field through interview techniques with banana farmers and distributing questionnaires to several banana farmers. The stage of this research was secondary data collection from the Rejang Lebong Regency Agriculture Office, then field exploration to obtain primary data in the field, both quantitatively and qualitatively. The exploration results showed that there were 5 genotypes of Rejang Lebong local Ambon bananas, namely green Ambon, yellow Ambon, Rejang Ambon, cold Ambon, and white Ambon. It is necessary to propagate banana seeds from tissue culture.